Risk factors for dysfunctional grief and functional impairment for all causes of death during the COVID-19 pandemic: The mediating role of meaning - Breen, Lauren; Mancini, Vincent; Lee, Sherman; Pappalardo, Emily; Neimeyer, Robert (Taylor & Francis, 2021)
The COVID-19 pandemic, coupled with significant social changes due to legislative and public health requirements, has changed the way in which people experience grief. We examined whether dysfunctional grief symptoms, disrupted meaning, risk factors, and functional impairment differed between people bereaved from COVID-19 and from other natural or violent causes in this same period. A sample of 409 participants (67.73% male; M = 37.54 years) completed an online survey in June 2021. There were no statistically significant differences between the three groups on any of the outcome variables; all three groups manifested clinical levels of functional impairment equal to or greater than bereaved groups diagnosed with complicated or prolonged grief disorder prior to the pandemic. Disrupted meaning partially mediated the relationship between risk factors on the one hand and functional impairment and dysfunctional grief symptoms on the other. Findings indicate that deaths during COVID-19, rather than deaths from COVID-19, may precipitate symptoms of significant clinical concern.